2001
DOI: 10.1525/aeq.2001.32.3.326
|View full text |Cite
|
Sign up to set email alerts
|

The Silencing of Latino Student “Voice”: Puerto Rican and Mexican Narratives in Eighth Grade and High School

Abstract: Narratives of 27 Puerto Rican and Mexican students, written first in eighth grade then again as juniors in high school, address the important question of "Who am I?" and illustrate school-sponsored silencing, with students' critiques of their educational experience ignored by both the elementary and the high school. The narratives also provide a window into the high dropout rates of Latino children, the reasons behind students" academic decisions, and interventions needed to change negative schooling processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 7 publications
0
48
0
4
Order By: Relevance
“…Often schools succumb to massive oversights in their curricula and pedagogy by erasing the different histories and social and economic realities of their students with only token nods to and discussions of difference (Banks, 2001;Delpit, 1997;Dempsey & Noblit, 1993;Flores-González, 2002;Pollock, 2004;Valenzuela, 1999). Also, we know that connections exist between students' social locations (e.g., their race, class, and immigrant status), culture, and how they learn (see King, 2005;Lee, 2007;Nasir & Hand, 2006 That is, particular policies of the school forced children to either assimilate and succeed or identify as Mexican American, be "silenced" and have their critiques of school ignored (Quiroz, 2001) and consequently disengage from school. Similarly, Flores-Gonzales (2002) describes the ways in which a Chicago school pushes Puerto Rican youth to either "street" or "school" identities; these identities in turn have implications for whether they drop out of high school.…”
Section: Race Ethnicity and The Cultural Ethos Of Schoolsmentioning
confidence: 99%
“…Often schools succumb to massive oversights in their curricula and pedagogy by erasing the different histories and social and economic realities of their students with only token nods to and discussions of difference (Banks, 2001;Delpit, 1997;Dempsey & Noblit, 1993;Flores-González, 2002;Pollock, 2004;Valenzuela, 1999). Also, we know that connections exist between students' social locations (e.g., their race, class, and immigrant status), culture, and how they learn (see King, 2005;Lee, 2007;Nasir & Hand, 2006 That is, particular policies of the school forced children to either assimilate and succeed or identify as Mexican American, be "silenced" and have their critiques of school ignored (Quiroz, 2001) and consequently disengage from school. Similarly, Flores-Gonzales (2002) describes the ways in which a Chicago school pushes Puerto Rican youth to either "street" or "school" identities; these identities in turn have implications for whether they drop out of high school.…”
Section: Race Ethnicity and The Cultural Ethos Of Schoolsmentioning
confidence: 99%
“…Because of my long-term setting engagement and my commitment to the study participants, the results cannot be adequately understood without including how I, the second author of this paper, functioned as a participant-observer (Louitzenheiser, 2002;Peshkin, 1988;Quiroz, 2001). Indeed, my social location--as a young African American woman researcher from a lower middle class background--informs how I understand the research.…”
Section: Situating the Ethnographermentioning
confidence: 99%
“…In a qualitative study of eighth-grade and high school journals, Quiroz (2001) found that these journals contained highly personal perspectives of classroom teachers.…”
Section: Appropriate Pedagogymentioning
confidence: 99%
“…The journals showed that from a generally optimistic view of school and their future careers in the eighth-grade, by eleventh-grade these students views shifted to generally negative, hopeless views of school and careers. As Quiroz (2001) reminds educators, for a voice to be empowering, it must be heard.…”
Section: Appropriate Pedagogymentioning
confidence: 99%